The Siri Strategy's Value in Managing the Bugis Family Economy in Surumana Village, South Banawa District, Donggala Regency - Maddukelleng, Maddukelleng; Muhammad, Wahid (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
Many people regard "siri" as having a bad connotation, which does not bode well for the Bugis. Because "siri" is frequently associated with violence and murder, the slogan "ejapi naeja" is frequently used (red later if you want red) It's always taken as a bloodbath. This value has become a sign associated with the Bugis ethnicity in every part of the country, even where the Bugis ethnicity is found. Siri culture is associated with a fighting attitude. Fight for justice, for humanity, and for the family's dignity. Many Bugis people are encouraged by Siri's ideals to work hard because they want to go on a pilgrimage as a mark of social prestige, and to work hard because they don't want to dishonor their families. If Siri is given room to think in the administration of the family economics, the dominance of the concept of decent value becomes an attractive positive value to be communicated. When it comes to revealing such events, a qualitative technique is ideal to apply because qualitative research takes place in a natural setting and aims to understand and interpret phenomena based on people's interpretations. Qualitative research involves the use and collection of various empirical materials, such as; personal experience, introspection, curriculum vitae, interviews, observations, historical, interactional and visual texts that describe routine and problematic moments, and their meaning in individual lives.